A kind of all-solid waste super-insulating geopolymer concrete and preparation method thereof

By using slag, fly ash, waste polyurethane foam and waste tire staple fibers in local polymer concrete, the greenhouse gas emission and solid waste treatment problems of the traditional silicate cement industry are solved, and high strength and ultra-separation are achieved The combination of thermal performance supports sponge city construction and green and sustainable development.

CN118439826BActive Publication Date: 2024-12-27JIANGSU CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410553844.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2024-12-27
Estimated Expiration
2044-05-07

AI Technical Summary

Technical Problem

Greenhouse gas emissions and natural resource consumption caused by the traditional silicate cement industry, as well as the problem of handling large amounts of construction solid waste and waste tires, a fully solid waste ultra-insulated polymer concrete is needed to achieve green and sustainable development and sponge. Urban construction.

Method used

Slag and fly ash are used as gelling materials, combined with waste polyurethane foam and waste tire staple fibers, and fully solid waste ultra-thermal insulation polymer concrete is prepared through specific ratios and process flows to improve its mechanical properties and durability.

Benefits of technology

It has achieved a combination of high strength and ultra-thermal insulation performance, reduced carbon dioxide emissions, realized waste reuse, and is suitable for the green and sustainable development of sponge urban construction and construction industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118439826B_ABST
    Figure CN118439826B_ABST
Patent Text Reader

Abstract

The present invention proposes a full solid waste super-insulating geopolymer concrete and a preparation method thereof, which belongs to the technical field of solid waste resource utilization and geopolymer concrete preparation. The raw materials in the geopolymer concrete include: waste polyurethane foam, cementitious material, waste tire short fiber (SWF), expanded vermiculite powder and alkali activator. The full solid waste super-insulating geopolymer concrete prepared by the present invention can maintain high strength while achieving high thermal insulation. At the same time, the use of waste polyurethane foam and waste tire short fiber can effectively improve the mechanical properties and durability of geopolymer concrete, and slag and fly ash are used as cementitious materials to reduce carbon dioxide emissions, providing support for sponge city construction and green and sustainable development of the construction industry at the material level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid waste resource utilization and geopolymer concrete preparation, and in particular relates to a full-solid waste super-insulating geopolymer concrete and a preparation method thereof. Background Art

[0002] As global seasonal changes intensify, promoting sponge city construction has become an innovative way to build water-resilient cities. At the same time, due to the large amount of greenhouse gas emissions and natural resource consumption caused by the traditional silicate cement industry, the use of alternatives such as slag and fly ash as cementitious materials has provided the industry with the possibility of sustainable green development. And with the demolition of abandoned buildings, a large amount of construction solid waste needs to be dealt with urgently.

[0003] In addition, my country's automobile industry has been booming in recent years, and a large number of waste tires are generated every year. If traditional incineration or open-air dumping is adopted, it will not only cause a large amount of environmental resources and land resources to be wasted, but also the fibers in the waste tires cannot be reused. In addition, scrapped car seats contain a large amount of polyurethane foam, which has excellent thermal insulation function.

[0004] Therefore, there is an urgent need to provide a full-solid waste super-insulating geopolymer concrete that can better serve the construction of sponge cities, realize the green and sustainable development planning of the concrete industry, and meet the needs of construction waste treatment. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a full solid waste super-insulating geopolymer concrete and a preparation method thereof. The full solid waste super-insulating geopolymer concrete prepared by the present invention can achieve super-insulation while maintaining high strength; among them, using slag and fly ash as cementitious materials can reduce carbon dioxide emissions, and adding waste polyurethane foam and waste tire short fibers can effectively improve the mechanical properties and durability of geopolymer concrete, achieving the effect of 1+1>2. Provide support for sponge city construction and green and sustainable development of the construction industry at the material level.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A full-solid waste super-insulating geopolymer concrete, comprising the following raw materials in parts by weight:

[0009] 60-70 parts of waste polyurethane foam and 30-40 parts of cementitious materials;

[0010] Wherein, according to mass percentage, the cementitious material includes 20-30% fly ash, 60-70% slag, and 5-10% silica fume.

[0011] Preferably, it also includes: short fibers from waste tires, expanded vermiculite powder and an alkali activator;

[0012] Wherein, the amount of the expanded vermiculite powder is 1 to 3% of the total mass of the waste polyurethane foam and the gelling material;

[0013] The ratio of the volume of the alkali activator to the total mass of the waste polyurethane foam and the gelling material is 300-500 mL: 1 kg;

[0014] The mixing amount of the waste tire short fibers is 1%-3% of the volume of the gelling material.

[0015] Beneficial effect: Within the range of various raw material types and usage ratios specified in the present invention, the compressive strength, tensile strength and thermal insulation performance of the final prepared concrete can be effectively improved; if the raw material types and usage ratios are not within the above-specified range, the final prepared concrete will not be able to obtain the best thermal insulation effect.

[0016] Furthermore, the waste tire short fibers include nylon 6 short fibers and nylon 66 short fibers;

[0017] Wherein, the mass ratio of the nylon 6 staple fiber to the nylon 66 staple fiber is 1:1.

[0018] Preferably, the preparation process of the alkaline activator is as follows: first, prepare an aqueous sodium hydroxide solution with a concentration of 8 mol / L, and let it stand for 24 hours; then add it to an aqueous sodium silicate solution (degrees Baume 40), and stir evenly to obtain the alkaline activator;

[0019] Wherein, the mass ratio of the sodium hydroxide aqueous solution to the sodium silicate aqueous solution is 3:7.

[0020] Preferably, the particle size of the waste polyurethane foam is 5 to 20 mm;

[0021] The fly ash contains more than 50 wt.% Al2O3 and SiO2, and has a specific surface area of ​​600-800 m 2 / kg, 45μm square hole sieve residue less than 1%;

[0022] The slag has a moisture content of less than 1% and a specific surface area of ​​380 to 410 m 2 / kg;

[0023] The silica fume has a particle size of 0.1 to 0.3 μm and a specific surface area of ​​15,000 to 30,000 m 2 / kg.

[0024] Preferably, the bulk density of the expanded vermiculite powder is 50 to 200 kg / m 3 , and the maximum operating temperature is 1100℃, with excellent thermal insulation performance.

[0025] Technical solution 2:

[0026] A method for preparing all-solid waste super-insulating geopolymer concrete comprises the following steps:

[0027] Weigh the above raw materials according to their usage, mix and stir to obtain all-solid waste geopolymer concrete slurry;

[0028] The all-solid waste geopolymer concrete slurry is transferred into a mold and demoulded after curing to obtain the all-solid waste super-insulating geopolymer concrete.

[0029] Preferably, the specific process of the mixing and stirring is:

[0030] The fly ash, slag, silica fume and expanded vermiculite powder are stirred and mixed once, and then the waste polyurethane foam and waste tire short fibers are added and stirred and mixed for a second time to obtain a solid mixture;

[0031] The alkali activator is added to the solid mixture and stirred for three times to obtain the all-solid waste geopolymer concrete slurry.

[0032] Furthermore, the rotation speed during the stirring and mixing process is 300-500 r / min; the stirring time is 2 min;

[0033] The secondary stirring and mixing speed is 300-500r / min; the stirring time is 1min;

[0034] The rotation speed of the three stirring and mixing is 300-500 r / min; and the stirring time is 4-6 min.

[0035] Preferably, the curing condition is curing at room temperature for 24 hours.

[0036] Compared with the prior art, the present invention has the following advantages and technical effects:

[0037] The present invention uses a mixture of fly ash, silica fume and slag in a certain ratio as a cementing material, and forms a full-solid waste super-insulating geopolymer concrete with waste polyurethane foam and waste tire short fibers. Among them, the cementing material, as an inorganic cementing material, has good bonding properties with waste polyurethane foam, thereby taking into account both thermal insulation and strength; the waste tire short fibers can diffuse and evenly distribute the stress in the geopolymer concrete, and connect the cracks in the matrix to prevent the expansion of the cracks.

[0038] The invention makes full use of waste polyurethane foam and waste tire short fibers to achieve waste recycling; the raw materials are easy to collect and the invention has the advantage of being green and environmentally friendly compared to traditional silicate concrete.

[0039] The geopolymer concrete prepared by the present invention has the advantage of strong bonding, can achieve bonding between waste polyurethane foams, and has the advantage of super heat insulation compared with traditional concrete.

[0040] The geopolymer concrete prepared by the present invention improves the applicability of the concrete in severe cold regions because a small amount of expanded vermiculite powder and waste polyurethane foam are present in the raw materials used.

[0041] The thermal insulation of the all-solid waste super-insulating geopolymer concrete prepared by the above preparation method is higher than that of ordinary insulating concrete, and this preparation process does not involve heating and other conditions, is simple to operate, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0043] Figure 1 This is a schematic flow chart of the method for preparing all-solid waste super-insulating geopolymer concrete in Example 1 of the present invention. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] The invention discloses a full-solid waste super-insulating geopolymer concrete, wherein the raw materials include 60-70 parts by weight of waste polyurethane foam, 30-40 parts of cementitious materials, short fibers of waste tires, expanded vermiculite powder and an alkali activator;

[0050] Calculated by mass percentage, the cementitious material includes 20-30% fly ash, 60-70% slag, and 5-10% silica fume.

[0051] Beneficial effects: Excessive fly ash leads to low activity, while too little fly ash leads to poor fluidity; excessive slag leads to flash solidification, while too little slag leads to poor early strength; excessive silica fume leads to poor economy, while too little silica fume leads to insufficient system density.

[0052] In some preferred embodiments, the added amount of expanded vermiculite powder is 1-3% of the total mass of the waste polyurethane foam and the gelling material.

[0053] Beneficial effects: Expanded vermiculite powder has high chemical stability and is commonly used in thermal insulation layers of various buildings, transportation, pipelines, containers, etc. It has good thermal insulation performance and high temperature resistance. The invention limits the addition amount of expanded vermiculite powder to 1-3% of the total mass of waste polyurethane foam and gelling material.

[0054] In some preferred embodiments, the total mass of waste polyurethane foam and gelling material: the volume of the alkali activator is 1 kg: 300-500 mL.

[0055] In some preferred embodiments, the waste polyurethane foam is taken from waste car seats, and the particle size is 5 to 20 mm;

[0056] In some preferred embodiments, the bulk density of expanded vermiculite powder is 50-200 kg / m 3 .

[0057] In some preferred embodiments, the alkaline activator is prepared by mixing 8 mol / L sodium hydroxide aqueous solution and sodium silicate aqueous solution in a mass ratio of 3:7, wherein the solute of the sodium silicate aqueous solution is Na2O·nSiO2, and n is selected from 1.5 to 3.5.

[0058] In some preferred embodiments, Al2O3 and SiO2 account for more than 50wt% of the fly ash, and the specific surface area is 600-800m 2 / kg, 45μm square hole sieve residue is less than 1%.

[0059] In some preferred embodiments, the slag has a moisture content of less than 1% and a specific surface area of ​​380 to 410 m 2 / kg.

[0060] In some preferred embodiments, the silica fume particle size is 0.1-0.3 μm, and the specific surface area is 15000-30000 m 2 / kg.

[0061] In some preferred embodiments, the waste tire short fibers include nylon 6 short fibers and nylon 66 short fibers; the mass ratio of the two is 1:1.

[0062] In addition, the present invention also provides a method for preparing all-solid waste super-insulating geopolymer concrete, comprising the following steps:

[0063] (1) mixing fly ash, slag, silica fume and expanded vermiculite powder at a low speed, adding waste polyurethane foam and waste tire short fibers, and mixing to obtain a solid mixture;

[0064] (2) adding an alkali activator to the solid mixture and stirring to obtain a full-solid waste geopolymer concrete slurry;

[0065] (3) The all-solid waste geopolymer concrete slurry is transferred into a mold, cured, and then demolded to obtain the all-solid waste super-insulating geopolymer concrete.

[0066] In some preferred embodiments, the low speed stirring in step (1) is specifically 300-500 r / min;

[0067] In some preferred embodiments, the curing condition in step (3) is curing at room temperature for 24 hours.

[0068] All raw materials used in the examples of the present invention are purchased from commercial sources. Among them, in the following examples of the present invention, the sources of raw materials used are:

[0069] Fly ash: from power plants, with a specific surface area of ​​600-800m 2 / kg, 45μm square hole sieve residue less than 1%;

[0070] Slag: from iron smelting plant, dried to a moisture content of less than 1%, ground to a specific surface area of ​​380-410m 2 / kg;

[0071] Silica fume: particle size distribution range is 0.1-0.3 μm, specific surface area is 15000-30000 m2 / kg;

[0072] Waste polyurethane foam: industrial grade, purchased from Suzhou Suxie Company, particle size between 5-20mm;

[0073] Expanded vermiculite powder: purchased from the market, with a bulk density of 50-200 kg / m 3 ;

[0074] Alkaline activator: prepare 8 mol / L NaOH solution and Na2O·2SiO2 aqueous solution in a mass ratio of 3:7;

[0075] Waste tire short fibers: including nylon 6 short fibers and nylon 66 short fibers;

[0076] Among them, the density of nylon 6 short fiber is 1.12g / cm 3 , melting point is 219℃, tensile strength is 60MPa, elongation at break is 100%, bending strength is 90MPa; nylon 66 short fiber density is 1.15g / cm 3 , melting point is 259℃, tensile strength is 70MPa, elongation at break is 40%, and flexural strength is 71.8MPa.

[0077] Unless otherwise specified, the “parts” used in the embodiments of the present invention are “parts by weight”.

[0078] The technical solution of the present invention is further illustrated by the following embodiments.

[0079] Example 1

[0080] The raw materials were weighed according to the following mass proportions: 30 parts of cementitious material (by mass percentage, 30% fly ash, 60% slag, 10% silica fume), 70 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the volume ratio of the total mass of waste polyurethane foam and cementitious material to the alkali activator is 1kg:500mL), and short fibers from waste tires (2% of the volume content).

[0081] The preparation method is as follows (see the specific flow chart Figure 1 ):

[0082] (1) Fly ash, slag, silica fume and expanded vermiculite powder were added to a stirrer at 300 rpm and stirred for 2 minutes; waste polyurethane foam and waste tire short fibers were added and stirred for 1 minute, and then an alkali activator was slowly added and stirred evenly for 6 minutes to obtain a full-solid waste geopolymer concrete slurry.

[0083] (2) The all-solid waste geopolymer concrete slurry was transferred into a steel mold with a size of 70.7×70.7×70.7 mm, vibrated for 60 seconds using a table vibrator to remove bubbles, and smoothed with a trowel.

[0084] (3) After curing for 24 hours at room temperature, the geopolymer can be demoulded (due to the effect of slag, the early strength of the geopolymer is high and it is easy to shape).

[0085] Example 2

[0086] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 30 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 70 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (the volume content is 1%).

[0087] Example 3

[0088] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 30 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 70 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (volume dosage is 0%).

[0089] Example 4

[0090] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 35 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, and 10% silica fume), 65 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (the volume content is 2%).

[0091] Example 5

[0092] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 35 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, and 10% silica fume), 65 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (the volume content is 1%).

[0093] Example 6

[0094] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 35 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 65 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (volume dosage 0%).

[0095] Example 7

[0096] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 40 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 60 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (2% of the volume content).

[0097] Example 8

[0098] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 40 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 60 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (volume dosage 1%).

[0099] Example 9

[0100] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 40 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 60 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (volume dosage 0%).

[0101] Example 10

[0102] The same as Example 1, except that the raw materials are weighed according to the following mass fractions: 40 parts of cementitious material (by mass fraction, 30% fly ash, 60% slag, 10% silica fume), 60 parts of waste polyurethane foam, expanded vermiculite powder (2% of the total mass of cementitious material and waste polyurethane foam), alkali activator (the ratio of the total mass of waste polyurethane foam, cementitious material and alkali activator is 1kg:500mL), and short fibers from waste tires (3% by volume).

[0103] Effect verification

[0104] Performance test experiment: Super-insulating geopolymer concrete was prepared according to the method in each embodiment, and the following performance tests were performed on it:

[0105] (1) The thermal conductivity shall be tested in accordance with the test method specified in GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulation Materials";

[0106] (2) The compressive strength and tensile strength are tested in accordance with GB / T500-81-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0107] The test results are shown in Table 1.

[0108] Table 1

[0109]

[0110]

[0111] Conclusion: By comparing Examples 1-3, 4-6 and 7-10, it can be found that as the volume content of waste tire short fibers gradually increases, the compressive strength and tensile strength of the material are improved. Therefore, the volume content of waste tire short fibers at 2% can maximize the compressive strength and tensile strength. In addition, by comparing Example 1, Example 4 and Example 7 (or Example 2, Example 5 and Example 8, or Example 3, Example 6 and Example 9), it can be found that as the waste polyurethane foam decreases, the strength of the concrete decreases slightly, but not significantly, and the thermal conductivity gradually increases. Therefore, if you want to obtain a material with super insulation and high strength, the best solution is Example 1, that is, using 70 parts by weight of waste polyurethane foam and 2% by volume of waste tire short fibers.

[0112] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A full solid waste super-insulating geopolymer concrete, characterized in that: In terms of weight parts, the raw materials are: 60-70 parts of waste polyurethane foam, 30-40 parts of cementitious materials, short fibers from waste tires, expanded vermiculite powder and alkali activator; Wherein, in terms of mass percentage, the cementitious material is: fly ash 20-30%, slag 60-70%, silica fume 5-10%; The amount of expanded vermiculite powder used is 1 to 3% of the total mass of waste polyurethane foam and gelling material; The amount of the waste tire short fibers added is 1-3% of the volume of the cementitious material.

2. The all-solid waste super-insulating geopolymer concrete according to claim 1, characterized in that: The waste tire short fibers include nylon 6 short fibers and nylon 66 short fibers.

3. The all-solid waste super-insulating geopolymer concrete according to claim 2, characterized in that: The mass ratio of the nylon 6 staple fibers to the nylon 66 staple fibers is 1:

1.

4. The all-solid waste super-insulating geopolymer concrete according to claim 1, characterized in that: The bulk density of the expanded vermiculite powder is 50-200 kg / m 3 .

5. A method for preparing all-solid waste super-insulating geopolymer concrete, characterized in that: The following steps are involved: Weigh the raw materials according to any one of claims 1 to 4, mix and stir to obtain a full-solid waste geopolymer concrete slurry; The all-solid waste geopolymer concrete slurry is transferred into a mold and demoulded after curing to obtain the all-solid waste super-insulating geopolymer concrete.

6. The method for preparing a full-solid waste super-insulating geopolymer concrete according to claim 5, characterized in that: The rotation speed during the stirring process is 300-500r / min, and the stirring time is 1-6min.

7. The method for preparing all-solid waste super-insulating geopolymer concrete according to claim 5, characterized in that: The curing conditions are room temperature curing for 24 hours.